Prevalence of problematic eating behavior and assessment of awareness on eating disorder among medical students - Aayush Priyam; Sudipta K. Das; Swayanka Samantray; Jayaprakash R. Ravan; Jigyansa I. Pattnaik (Industrial Psychiatry Journal)
Background: There are few studies that highlight the problematic eating behavior of college students; however, similar data on the medical undergraduate population is sparse, especially in India. Awareness among medical students would be considered different compared to other students, owing to their training and education. Aim: To know the prevalence of problematic eating behavior in medical undergraduate students and to measure the extent of awareness regarding problematic eating behavior present amongst the students. Materials and Methods: The present study was a cross-sectional study conducted over 2 months that included students (1st -4th year and interns) aged 17–30 years, studying MBBS. Ethical approval to do the study was taken from the Institutional Ethics Committee. Purposive sampling was done. Those students who gave informed consent to be a part of this study and were not diagnosed with any severe mental and physical illness were included in this study. Socio-demographic data was collected in a semi-structured proforma. The questionnaire was given to the students to fill up. The questionnaire included EAT-26 (Eating Attitudes Test-26) score for screening the students for problematic eating behavior. For objectively assessing awareness amongst the students regarding the same, a few questions of knowledge, attitude, and practice (KAP) on problematic eating were included in the form. The result was analyzed using SPSS- 25 (Statistical Package for Social Sciences) and appropriate statistical tests. Results: Among Medical undergraduates, 19.9% had EAT-26 score more than or equal to 20, suggesting some problematic eating behavior. A total of 36.7% of students were obese, while 5.6% were underweight. Gender and background do not play any role in the causation of Problematic Eating Behaviour (PEB). There was a significant difference in the EAT score with respect to the education of the head of the family (P < 0.01), positive history of mental illness in the family (P = 0.01), positive history of childhood obesity (P < 0.01), and positive history of bullying (P < 0.01). Awareness or knowledge about eating disorders is high among MBBS graduates, which could be a protective factor in general. Conclusion: Obesity is a more concerning issue in the medical undergraduate population rather than underweight. Childhood obesity and bullying emerge as important factors affecting the eating attitudes and behavior among medical graduates